Profile of investors in Singapore - Goh, Hui Yang (2015)
Investment is gaining its popularity in Singapore. As the Singapore Government encourages Singaporeans to invest (especially in shares), there is an increased number of investors in the market recently. The objective of this study is to look into the profile of investors in Singapore. The demographic characteristics, attitude and perception of investors towards the different types of financial instruments and financial services will be examined. To achieve the stated objective, a survey was carried out. Questionnaires were administered to a sample of 300 investors who have experience with at least one type of financial instruments. Using a statistical program, the data gathered were analyzed. Some limitations of this study were highlighted and recommendations were made to facilitate future research.